Hysteresis models for response history analyses of recycled rubber–fiber reinforced bearings (RR-FRBs) base isolated buildings. (1st January 2019) - Calabrese, A.; Spizzuoco, M.; Strano, S.; Terzo, M.
Highlights: Low performance elastomers for base isolation. RR-FRBs have a robust behavior, and good re-centering capabilities. RR-FRBs are effective in reducing the lateral response of low rise buildings. The bilinear and the Bouc and Wen models of hysteresis for RR-FRBs. Abstract: The aim of this study is to assess the applicability of two well-known hysteresis models for the prediction of the response of a Recycled Rubber – Fiber Reinforced Bearings (RR-FRBs) base isolated building under ground motion excitation. Results of experimental tests on low-cost rubber bearings are used to determine their response under cyclic loading, and to derive the parameters of the Bilinear and the Bouc–Wen hysteresis models using consolidated procedures. Response History Analyses (RHAs) are then performed to assess the behavior of a prototype building when base isolated with the low-cost devices. The outputs of RHAs are then compared to shaking table test results to validate the capability of the hysteresis models of predicting the peak structural responses under ground motion excitations. Findings of this research confirm the advantages of using low-cost rubber devices for earthquake hazard mitigation. The potentials and limitations of adopting simple models of hysteresis when assessing the seismic response of a RR-FRBs base isolated structure are discussed in this study.